2020
DOI: 10.1017/dmp.2020.437
|View full text |Cite
|
Sign up to set email alerts
|

Conducting COVID-19-Related Research in Jordan: Are We Ready?

Abstract: The Coronavirus Disease-2019 (COVID-19) pandemic is a public health emergency of international concern. This pandemic poses a challenge to research and scientific community. In this study, we developed and tested content reliability and content validity of a questionnaire designed for evaluating the readiness and willingness of researchers to participate in virology research in Jordan. The survey was hosted on an online platform, and the link was emailed. A total of 332 participants from universities across Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In terms of research and community service, although regulations from the relevant ministries provide a fairly high degree of flexibility by allowing delays, changes in locations and methods as well as changes in focus to issues related to COVID-19, there have been obstacles in the implementation of research such as laboratory closures, refusal of informants and the rejection of society as a subject of study and community service. The constraints related to research and community service that we found in this study were more on the technical constraints of implementing the activities and in the end, these obstacles could be overcome by making various adjustments and arrangements [41].…”
Section: Discussionmentioning
confidence: 89%
“…In terms of research and community service, although regulations from the relevant ministries provide a fairly high degree of flexibility by allowing delays, changes in locations and methods as well as changes in focus to issues related to COVID-19, there have been obstacles in the implementation of research such as laboratory closures, refusal of informants and the rejection of society as a subject of study and community service. The constraints related to research and community service that we found in this study were more on the technical constraints of implementing the activities and in the end, these obstacles could be overcome by making various adjustments and arrangements [41].…”
Section: Discussionmentioning
confidence: 89%
“…It was reported by Ikhmais et al [27] that the readiness of researchers in Jordan to participate in viral research is low, due to barriers including the limited facilities and well-equipped laboratories for viral research and limited knowledge of virology [28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This did not help with the interpretation of the findings rather than being a limitation to the conduction of the study. Studies show that questionnaire design choices, such as handling 'I do not know' may impact the level of non-response answers [27]. In addition, it is reported that forcing all questions to be answered affects the level of non-response and thus it is advised to avoid this; likewise, offering an explicit option is also not recommended as these options strongly increase non-response.…”
Section: Discussionmentioning
confidence: 99%
“…No pseudovirus-based studies are being or have been performed in Jordan. To our knowledge, there are no basic virology laboratories where viruses are being studied, produced and stored in the country's academic institutions [11]. Despite the remarkably few numbers of basic virologists and immunologists in Jordanian universities and research centers, we believe that the problem of lack of basic virology and immunology research in the country is more than lack of facilities and resources.…”
Section: Poor Funding Is the Main Obstacle Faced By Biomedical Resear...mentioning
confidence: 99%